Unruh effect for mixing neutrinos - Cozzella, Gabriel [UNESP]; Fulling, Stephen A.; Landulfo, André G. S.; Matsas, George E. A. [UNESP]; Vanzella, Daniel A. T. (American Physical Society (APS), 2018)
Recently, the inverse β-decay rate calculated with respect to uniformly accelerated observers (experiencing the Unruh thermal bath) was revisited. Concerns have been raised regarding the compatibility of inertial and accelerated observers' results when neutrino mixing is taken into account. Here, we show that these concerns are unfounded by discussing the properties of the Unruh thermal bath with mixing neutrinos and explicitly calculating the decay rates according to both sets of observers, confirming thus that they are in agreement. The Unruh effect is perfectly valid for mixing neutrinos.